Landscapes of Memories:: Visual and Spatial Dimensions of Hajja's Narrative of Self - Willemse, Karin (Narrative Matters, 2012)
In this article, the focus is on how to represent narratives of self well. This dilemma concerns the specific narrative of self of Hajja, a market woman who lived in the provincial town of Kebkabiya, North Darfur, Sudan. The challenge of "responsible representation" in relation to her narrative concerns the question of how to represent a narrative that does not follow the expected structure of such a narrative. By considering the narrative as a performance of identities in the discursive and material context of narration, the author points out that a narrative is part and parcel of its context of narration. A representation of that narrative should therefore include elements of this context. Not only the discursive and verbal, but also the visual, spatial, and ultimately the temporal dimensions of the context allow us to understand narratives as enactments of self in a specific context. This consideration ties into the current debate on the nature of narrative. Narratives should not only be understood in terms of the what and how, but also in relation to the where and when of their narration. Narratives constitute spaces that allow the narrator a temporal moment of closure, of constructing oneself as a unified, coherent, bounded self in a specific place at a specific time.